2011
DOI: 10.1167/iovs.10-6005
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Improves Retinal Ganglion Cell Survival and Spatial Vision after Acute Retinal Ischemia/Reperfusion in Mice

Abstract: This specific combination of behavioral measurements of visual function, cortical activity imaging, and histologic analyses is ideally suited to follow ischemia-induced changes and to monitor the effect of therapeutic approaches. Statin therapy may be a promising pharmacologic tool for the treatment of acute retinal ischemia in particular because, in our study, simvastatin was applied after ischemia, a treatment regimen with much greater clinical relevance than preventive administration, as in previous studies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Sun et al also demonstrated that Cobalt protophorphyrin-induced Heme Oxygenase-1 attenuated I/R induced injury in retina [49]. The hypolopodemic drug Simvastatin also improved retinal ganglion cell survival in mouse model of retinal I/R injury [50]. More recently, Fujita et al showed that pharmacological blocking of Angiotensin II type 1 receptor signaling produced neuroprotection via suppression of ROS production [51].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al also demonstrated that Cobalt protophorphyrin-induced Heme Oxygenase-1 attenuated I/R induced injury in retina [49]. The hypolopodemic drug Simvastatin also improved retinal ganglion cell survival in mouse model of retinal I/R injury [50]. More recently, Fujita et al showed that pharmacological blocking of Angiotensin II type 1 receptor signaling produced neuroprotection via suppression of ROS production [51].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Briefly, mice were anesthetized with an intraperitoneal injection of 5% chloral hydrate in phosphate-buffered saline (PBS; 500 mg/kg body weight; Fluka, Seelze, Germany). After application of topical anesthesia (oxybuprocaine-hydrochloride 4 mg/mL; Bausch & Lomb GmbH, Feldkirchen, Germany), the anterior chamber of the right eye was cannulated with a 30-gauge needle connected to an elevated normal saline reservoir.…”
Section: Transient Retinal Ischemiamentioning
confidence: 99%
“…Our results are in agreement with previous studies. 19,20 Immunostaining and Evaluation of RGC Numbers…”
Section: Transient Retinal Ischemiamentioning
confidence: 99%
“…Therefore, using the aforementioned behavioral techniques in rodent models that display disease etiology that is similar to humans, such as the DBA/2 mouse, allows us to conduct studies that obtain valuable information on disease mechanisms and therapeutic strategies at considerably lower cost with more data points. We can use these techniques in mice to evaluate therapeutic intervention in rodent models of disease (Adamus et al, 2012; Cahill et al, 2011; Krempler et al, 2011; Savigni et al, 2013), and RGC axon regeneration (de Lima et al, 2012), test variables such as age and gender (van Alphen et al, 2009), neuronal and RGC disease mechanisms in glaucomatous mice (Burroughs et al, 2011; Feng et al, 2013; Kaja et al, 2011), similar to the assessment of visual deficits in other animal models of disease (Pinto et al, 2007; Pinto et al, 2005; Puk et al, 2009; Richards et al, 2008; Roeser and Baier, 2003; Schmucker and Schaeffel, 2006; Umino and Solessio, 2013). Such data contribute to the pre-clinical development of promising therapeutic interventions prior to human clinical trials and benefit from their non-invasive and comprehensive nature resembling many of the aspects of human clinical trials.…”
Section: Clinical Relevance Of Data Derived From Behavioral Assaysmentioning
confidence: 99%